Asthma “Control” - Nick R Anthonisen (Canadian Respiratory Journal)
In this issue of the Canadian Respiratory Journal, Cowie et al (pages 555-558) make the startling claim that "inhaled corticosteroid therapy does not control asthma". This sounds crazy: if inhaled steroids don't control asthma, what does? It turns out not to be crazy. Cowie et al reported on the effectiveness of asthma control according to Canadian guidelines (1) in several large groups of asthmatics evaluated by cross-sectional, one-point-in-time questionnaires. They found that patients on inhaled steroids were less well-controlled than those who were not on inhaled steroids, and that there was a dose effect, in that the larger the dose of inhaled steroids the worse the control. There is, of course, a simple explanation for this; patients with hard-to-control asthma are likely to be prescribed inhaled steroids, and the harder the disease is to control, the higher the dose. However, these findings are compatible with inhaled steroids having a minor effect on asthma control, something that we do not believe (2). There are excellent data from clinical trials (3) that inhaled steroids work, and in population studies (4), their use is associated with improved survival.